PENGARUH SOCIAL MEDIA MARKETING DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Resto Cimaci Grill Sumenep) - Sri Suciawati Rohma; Edy Purwanto (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2026)
Marketing strategy is very important for various business sectors. This marketing strategy greatly influences the development and sustainability of a business. There needs to be an understanding of how effective marketing strategies are needed by companies to provide the needs and desires desired by customers.This study was conducted to test the effect of Social Media Marketing and Service Quality on Repurchase Intention through Customer Satisfaction as an intervening variable. The population in this study were consumers who had visited, purchased, and consumed food products at Resto Cimaci Grill Sumenep whose number was unknown. The sample used in this study was 100 respondents. The data analysis method used was Smart PLS with the PLS-SEM method. The results of the study indicate that: Social Media Marketing does not have a positive and significant effect on repurchase interest at Cimaci Grill Sumenep restaurant, Service Quality has a positive and significant effect on repurchase interest at Cimaci Grill Sumenep restaurant, Customer Satisfaction has a positive and significant effect on repurchase interest at Cimaci Grill Sumenep restaurant, Social Media Marketing has a positive and significant effect on customer satisfaction at Cimaci Grill Sumenep restaurant, Service Quality has a positive and significant effect on customer satisfaction at Cimaci Grill Sumenep restaurant, Social Media Marketing mediated by customer satisfaction does not have a positive and significant effect on repurchase interest at Cimaci Grill Sumenep restaurant, and Service Quality mediated by customer satisfaction has a positive and significant effect on repurchase intention at Cimaci Grill Sumenep restaurant.